Pharmacological approaches to pulmonary fibrosis following COVID-19 - Lassan, Stefan; Tesar, Tomas; Tisonova, Jana; Lassanova, Monika (Frontiers in Pharmacology, 2023)
Background: In the past few years, COVID-19 became the leading cause of morbidity and mortality worldwide. Although the World Health Organization has declared an end to COVID-19 as a public health emergency, it can be expected, that the emerging new cases at the top of previous ones will result in an increasing number of patients with post-COVID-19 sequelae. Despite the fact that the majority of patients recover, severe acute lung tissue injury can in susceptible individuals progress to interstitial pulmonary involvement. Our goal is to provide an overview of various aspects associated with the Post-COVID-19 pulmonary fibrosis with a focus on its potential pharmacological treatment options. Areas covered: We discuss epidemiology, underlying pathobiological mechanisms, and possible risk and predictive factors that were found to be associated with the development of fibrotic lung tissue remodelling. Several pharmacotherapeutic approaches are currently being applied and include anti-fibrotic drugs, prolonged use or pulses of systemic corticosteroids and non-steroidal anti-inflammatory and immunosuppressive drugs. In addition, several repurposed or novel compounds are being investigated. Fortunately, clinical trials focused on pharmacological treatment regimens for post-COVID-19 pulmonary fibrosis have been either designed, completed or are already in progress. However, the results are contrasting so far. High quality randomised clinical trials are urgently needed with respect to the heterogeneity of disease behaviour, patient characteristics and treatable traits. Conclusion: The Post-COVID-19 pulmonary fibrosis contributes to the burden of chronic respiratory consequences among survivors. Currently available pharmacotherapeutic approaches mostly comprise repurposed drugs with a proven efficacy and safety profile, namely corticosteroids, immunosuppressants and antifibrotics. The role of nintedanib and pirfenidone is promising in this area. However, we still need to verify conditions under which the potential to prevent, slow or stop progression of lung damage will be fulfilled.